Analisis Lingkungan Kerja Fisik Di Kantor Kelurahan Batu Jaya Kota Tangerang - Rizal Suti Hambawi; Dodi Prasada (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
Objective: To analyze the physical work environment at the Batu Jaya Village Office and its impact on employee performance and the quality of public service. This study employed a qualitative method. Qualitative methods were chosen because they aligned with the research objective, which was to obtain more in-depth information about the physical work environment at the Batu Jaya Village Office, Tangerang. Data collection techniques included direct observation, documentation, and interviews with employees as key informants.The analysis identified several problems, including cramped workspaces, dim lighting, poor air circulation, and a leaking roof during rain. These conditions resulted in decreased concentration, slowed performance, and decreased service quality. Employees suggested improvements to lighting, ventilation, room size, and maintenance of work facilities.